Kant on Love - Rinne, Pärttyli (Kantstudien-Ergänzungshefte, 2018)
What did Immanuel Kant really think about love? This book is the first in-depth study of the concept of love in Kant`s philosophy. It argues that love is much more important to Kant than previously thought, and that understanding love is actually essential for Kantian ethical life. Perhaps surprisingly, for Kant, love permeates human existence from the strongest impulses of nature to the highest ideals of morally deserved happiness.